Illuminating the importance of craftsmanship in compassionate caring and facilitating its development in student nurses - Adamson, Elizabeth (Edinburgh Napier University, 2021)
This thesis provides a critical reflection on my original contributions to knowledge in the field of nursing practice and nurse education over the last decade. Collectively my eight selected papers demonstrate an ongoing and incrementally developing conceptual approach. This culminates in the presentation, within my final capstone paper, of my original recombinant innovation. In this paper, application of the innovation is articulated through a compassionate craftsmanship relational model, which fuses multivalent ideas from the fields of compassionate care and craftsmanship. Combining these disparate and frequently tacit elements together required diligence and courage in a world where fixed solutions are increasingly prominent. My innovative relational model is, however, importantly designed to be used as a heuristic device to promote reflection within nurse education and compassionate care.

The papers are grouped into three sets. The initial group of papers focus on the nature of nursing expertise and compassionate care. They illuminate important elements of care practice made possible through possession and application of often hidden tacit knowledge stored up in the mind of the nurse. The implicit underpinning concepts revealed in this research became progressively more explicit and well-articulated over the ten-year period as I developed my approach and thinking in relation to similarities between compassionate nursing expertise and craftsmanship.

A second suite of papers shares a common methodological focus where qualitative approaches were used to gather stories in a novel way. The “emotional touch-points” method was used to capture stakeholder experiences of compassionate care and caring. The stories served as a powerful mechanism to gain insights into the lived experience of others. This approach held pragmatic value for patients, nurses and students, because the stories transformed thinking and motivated action, importantly feeding into the golden thread of compassionate craftsmanship.

The third set of papers demonstrates my interest in applying ideas from my practice-based research to educational environments by integrating the findings and stakeholder stories in a range of original pedagogical initiatives. Through implementation of these novel approaches, development in compassionate care and nursing ‘know-how’ was facilitated in student nurses. The educationally oriented papers articulate the positive impact and contribution to the fields of nursing and nurse education achieved through supporting learning in this area.